2023
DOI: 10.1101/2023.02.11.23285788
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ensemble learning for higher diagnostic precision in schizophrenia using peripheral blood gene expression profile

Abstract: The need for molecular biomarkers for schizophrenia has been well recognized. Recently, peripheral blood gene expression profiling and machine learning (ML) tools have become popular for biomarker discovery. The stigmatization associated with schizophrenia advocates the need for diagnostic models with higher precision. In this study, we propose a strategy to develop higher-precision ML models using ensemble learning. We performed a meta-analysis using peripheral blood expression microarray data. The ML models:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(53 reference statements)
0
0
0
Order By: Relevance
“…During the last few years, several studies have demonstrated the value and utility of transcriptome profiling of post-mortem tissues in unravelling pathophysiological mechanisms underlying ALS and supporting the existence of a molecular taxonomy for this disease [9,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. However, post-mortem analysis of ALS brain samples does not allow for evaluation of alterations occurring during the disease course; thus, it does not represent the optimal resource for biomarker discovery efforts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last few years, several studies have demonstrated the value and utility of transcriptome profiling of post-mortem tissues in unravelling pathophysiological mechanisms underlying ALS and supporting the existence of a molecular taxonomy for this disease [9,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. However, post-mortem analysis of ALS brain samples does not allow for evaluation of alterations occurring during the disease course; thus, it does not represent the optimal resource for biomarker discovery efforts.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, gene expression studies have been demonstrated to be powerful in providing valuable insights into the molecular basis underlying ALS pathophysiology and identifying molecular signatures or biomarkers able to classify ALS patients into selective clinically relevant subtypes characterized by different biological properties, prognostic biomarkers, and treatment options [14][15][16][17][18][19]. Within this context, the emerging use of machine learning approaches to find genetic biomarkers or construct robust disease classifiers based on patients' gene expression data is revolutionizing clinical decision-making in multiple complex human conditions, including cancer and cardiovascular diseases, and proving to be an exciting tool and promising option for hopefully improving our skills also in neurological conditions [20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%